2020
DOI: 10.3390/pharmaceutics12080734
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Study of Extracellular Vesicles Migration in Cartilage-Derived Osteoarthritis Samples Using Real-Time Quantitative Multimodal Nonlinear Optics Imaging

Abstract: Mesenchymal stromal cells (MSCs)-derived extracellular vesicles (EVs) are promising therapeutic nano-carriers for the treatment of osteoarthritis (OA). The assessment of their uptake in tissues is mandatory but, to date, available technology does not allow to track and quantify incorporation in real-time. To fill this knowledge gap, the present study was intended to develop an innovative technology to determine kinetics of fluorescent MSC-EV uptake by means of time-lapse quantitative microscopy techniques. Adi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 47 publications
3
15
0
Order By: Relevance
“…In this regard, it has been observed that the EVs derived from ASCs have the ability to fast penetrate for several micrometers into the cartilage, arriving predominantly at the matrix, but also reaching the cells. Herein presented results confirmed the quick EVs penetration along 30–40 μm depth already observed after a 5 h time-lapse in both micromasses and cartilage explants with the same technology [ 13 ], and further extended both intensity and spatial distribution measurements up to 16 h. Moreover, the observation of two diffusion kinetics of EVs suggests an active and steady initial process, followed by a more passive and slower one, which could be linked both to the differences in EVs penetration in the collagen-rich areas, but also to the progressive achievement of saturation, considering the 16 h as the identified time point when the signal reached a plateau. Finally, the highest EVs prevalence in ECM than in cells observed in experiments conducted on cartilage explants was not previously observed in micromasses [ 13 ], where a more homogenous EVs diffusion was reported.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…In this regard, it has been observed that the EVs derived from ASCs have the ability to fast penetrate for several micrometers into the cartilage, arriving predominantly at the matrix, but also reaching the cells. Herein presented results confirmed the quick EVs penetration along 30–40 μm depth already observed after a 5 h time-lapse in both micromasses and cartilage explants with the same technology [ 13 ], and further extended both intensity and spatial distribution measurements up to 16 h. Moreover, the observation of two diffusion kinetics of EVs suggests an active and steady initial process, followed by a more passive and slower one, which could be linked both to the differences in EVs penetration in the collagen-rich areas, but also to the progressive achievement of saturation, considering the 16 h as the identified time point when the signal reached a plateau. Finally, the highest EVs prevalence in ECM than in cells observed in experiments conducted on cartilage explants was not previously observed in micromasses [ 13 ], where a more homogenous EVs diffusion was reported.…”
Section: Discussionsupporting
confidence: 83%
“…Herein presented results confirmed the quick EVs penetration along 30–40 μm depth already observed after a 5 h time-lapse in both micromasses and cartilage explants with the same technology [ 13 ], and further extended both intensity and spatial distribution measurements up to 16 h. Moreover, the observation of two diffusion kinetics of EVs suggests an active and steady initial process, followed by a more passive and slower one, which could be linked both to the differences in EVs penetration in the collagen-rich areas, but also to the progressive achievement of saturation, considering the 16 h as the identified time point when the signal reached a plateau. Finally, the highest EVs prevalence in ECM than in cells observed in experiments conducted on cartilage explants was not previously observed in micromasses [ 13 ], where a more homogenous EVs diffusion was reported. These data evidencing differences in EVs kinetics between the two 3D in vitro models might be due to the different cell to matrix ratios and local homogeneity, both higher in micromasses, and suggest the use of cartilage specimens for kinetic studies being more representative of the real cartilage physiology.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations